Tradisi Islam Dalam Pembentukan Kepribadian Luhur Melalui Mekanisme Berfikir Untuk Menghadapi Dinamika Zaman - Neliwati Neliwati; Maisaroh Ritonga; Nursalimah Nursalimah (Indonesian Journal of Religion and Society, 2022)
Humans are the most glorious creatures created by Allah. Human life is controlled by imitation nature. Natural imitation created by human knowledge. Knowledge is significantly correlated with the emergence of technology products. Humans are enslaved and become dependent on technology. Technology affects the human mind which causes humans to focus more on the technology in their hands. Sensitivity and empathy are lost because of technology. Religion has a guiding function, besides that it also has the function of being a supporter of the harmony of life. The Islamic tradition through the schools of Islam found in aqidah is identical to the mechanism of thinking. The research aims to see how the mechanism of thinking in the Islamic tradition can forge a noble personality in the midst of the extreme challenges of the times. Mechanisms of thinking include planning, development, control, and utilization. The mechanism of thinking in the Islamic tradition in forging a noble personality in the midst of the extreme challenges of the times, planning is a medium for compiling and determining the stages and efforts to be made in forging a noble personality in the midst of the extreme challenges of the times. The planning and development system in forging a noble personality in the midst of the extreme challenges of the times must be able to see how the picture of development and technological sophistication in the future will be, and it is the task of planning to make adjustments to the system for forging a noble personality.